Islamic Ethics in Personal and Social Life Tolerance and Interfaith Dialogue in Islamic History - Hasballah Hasballah; Inayatillah Inayatillah (Civiliza Publishing, Indonesia., 2026)
This article examines historically the practice of tolerance and interreligious dialogue in Islamic civilization, starting from the period of the Prophet Muhammad (peace be upon him) in Medina, the era of the Umayyad and Abbasid Caliphate, to the plurality of al-Andalus (Islamic Spain). Using a historical-critical approach and analysis of primary and secondary sources, this study argues that tolerance in Islam is not just a pragmatic concession but has strong theological roots in the teachings of the Qur'an and Sunnah. The findings show that Muslim societies have historically succeeded in building a social ecosystem that allows for productive coexistence between Muslims, Christians, Jews, and adherents of other religions, which is manifested through legal mechanisms (dzimmi systems, interreligious agreements), intellectual (translation movements, philosophical debates), and culture (mutual influence in art, architecture, and science). This article also discusses the relevance of this historical heritage to contemporary interreligious dialogue discourse in the midst of the challenges of global radicalism and Islamophobia.